Big Cat Coalitions: A Comparative Analysis of Regional Brain Volumes in Felidae - Sakai, Sharleen T.; Arsznov, Bradley M.; Hristova, Ani E.; Yoon, Elise J.; Lundrigan, Barbara L. (Frontiers in Neuroanatomy, 2016)
Broad-based species comparisons across mammalian orders suggest a number of factors that might influence the evolution of large brains. However, the relationship between these factors and total and regional brain size remains unclear. This study investigated the relationship between relative brain size and regional brain volumes and sociality in 13 felid species in hopes of revealing relationships that are not detected in more inclusive comparative studies. In addition, a more detailed analysis was conducted of 4 focal species: lions (Panthera leo), leopards (Panthera pardus), cougars (Puma concolor), and cheetahs (Acinonyx jubatus). These species differ markedly in sociality and behavioral flexibility, factors hypothesized to contribute to increased relative brain size and/or frontal cortex size. Lions are the only truly social species, living in prides. Although cheetahs are largely solitary, males often form small groups. Both leopards and cougars are solitary. Of the four species, leopards exhibit the most behavioral flexibility, readily adapting to changing circumstances. Regional brain volumes were analyzed using computed tomography (CT). Skulls (n=75) were scanned to create three-dimensional virtual endocasts, and regional brain volumes were measured using either sulcal or bony landmarks obtained from the endocasts or skulls. Phylogenetic least squares (PGLS) regression analyses found that sociality does not correspond with larger relative brain size in these species. However, the sociality/solitary variable significantly predicted anterior cerebrum (AC) volume, a region that includes frontal cortex. This latter finding is despite the fact that the two social species in our sample, lions and cheetahs, possess the largest and smallest relative AC volumes, respectively. Additionally, an ANOVA comparing regional brain volumes in 4 focal species revealed that lions and leopards, while not significantly different from one another, have relatively larger AC volumes than are found in cheetahs or cougars. Further, female lions possess a significantly larger AC volume than conspecific males; female lion values were also larger than those of the other three species (regardless of sex). These results may reflect greater complexity in a female lion’s social world, but additional studies are necessary. These data suggest that within family comparisons may reveal variations not easily detected by broad comparative analyses.